Draft Genome Sequence of Xylella fastidiosa subsp. fastidiosa Strain Stag’s Leap - Chen, J. (Genome Announc, 2016)
Xylella fastidiosa subsp. fastidiosa causes Pierce’s disease of grapevine. Presented here is the draft genome sequence of the Stag’s Leap strain, previously used in pathogenicity/virulence assays to evaluate grapevine germplasm bearing Pierce’s disease resistance and a phenotypic assessment of knockout mutants to determine gene function.